DEVELOPMENT OF JUMP SERVE TRAINING MODELS ON ATHLETES - Resa Sukardi Massa (Universitas Negeri Gorontalo, 2020)
The purpose of this study is to develop a training model or variations of movements to be able to improve the ability to jump serveas a solution to overcome existing problems. This research uses Research and Development research methods. Small group trials are carried out with a sample of 6-12 male volleyball athletes. While the field trials were carried out on 30 volleyball male athletes. The results showed that the volleyball jump servetraining model was effective in developing the male volleyball jump serveability. The volleyball jump servetraining model developed and made by researchers is a product that aims to assist the trainer in developing volleyball jump servetraining programs, in an effort to improve the men's volleyball jump serveability, and as a reference for training materials.